2013
DOI: 10.1103/physrevb.87.035420
|View full text |Cite
|
Sign up to set email alerts
|

Artificially lattice-mismatched graphene/metal interface: Graphene/Ni/Ir(111)

Abstract: We report the structural and electronic properties of an artificial graphene/Ni (111) (111), and mildly corrugated graphene on Ir(111), allows to disentangle the two key properties which lead to the observed increased interaction, namely lattice matching and electronic interaction. Although the latter determines the strength of the hybridization, we find an important influence of the local carbon configuration resulting from the lattice mismatch.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
79
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 39 publications
(55 reference statements)
12
79
0
Order By: Relevance
“…For the present case of Co intercalation in graphene/Ir(111) [21][22][23][24], a considerable lattice mismatch occurs, similar to the case of an intercalated Ni layer [25], which on the one hand gives the opportunity to examine the electronic structure of thin metallic films under tensile stress, but also necessitates a close examination of the growth mode at the monolayer stage and beyond. Here we use C 1s and Ir 4f core-level photoemission to study the thickness and temperature dependence of Co interaction with graphene/Ir(111).…”
Section: B Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…For the present case of Co intercalation in graphene/Ir(111) [21][22][23][24], a considerable lattice mismatch occurs, similar to the case of an intercalated Ni layer [25], which on the one hand gives the opportunity to examine the electronic structure of thin metallic films under tensile stress, but also necessitates a close examination of the growth mode at the monolayer stage and beyond. Here we use C 1s and Ir 4f core-level photoemission to study the thickness and temperature dependence of Co interaction with graphene/Ir(111).…”
Section: B Resultsmentioning
confidence: 92%
“…We performed a separate experiment using Ni as intercalant, and assign this line, in analogy with the case of intercalated Ni, to the different adsorption geometries of the carbon atoms. Furthermore, investigating the properties of the graphene/Ni/Ir(111) system, Pacile et al [25] observe a strong asymmetry towards lower binding energy in the C 1s line shape, which indicates the presence of a second component as well. The fact that the spectra presented in [25] were measured at room temperature with lower resolution, whereas the spectra in Fig.…”
Section: B Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to grow G on FM, carbon segregation or chemical vapor deposition (CVD) of hydrocarbons on single crystals have been used so far [17][18][19]. Alternatively, single layers of Ni or Co atoms have been intercalated underneath G grown on Ir(111) [20,21], with the benefit of tailoring the structural properties at the interface. The bare G/Ir(111) system has been studied with several methods, all describing * daniela.pacile@fis.unical.it a gently rippled moiré superstructure where carbon atoms interact very weakly with the underlaying metal, thus keeping an almost unperturbed graphene π band [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recent papers have shown that interface properties highly depend on the lattice matching 65 or interface chemistry. 66 At Mg/MgH 2 interfaces, the Mg-H bonding is the most important bonding that leads to interface stability.…”
Section: The Search Of Relative Position Of Two Phasesmentioning
confidence: 99%